The potential analysis of a technopark in a freshwater fishery area in Dham Pulo Village, Aceh Besar - Zahara, Silvia; Putra, Dedi Fazrianyah; Jalil, Zulkarnain; Chan, Syafruddin (Acta Aquatica: Aquatic Sciences Journal, 2023)
Dham Pulo Village, located in the Aceh Besar district, has been engaged in freshwater aquaculture for 10 years. Fishery activities in this village already have a supply chain of fish seeds produced independently of expansion activities. Technological applications have also been applied, such as fish feed engineering and the use of Internet of Things (IoT) technology in feeding methods. This study aims to examine the potential of Dham Pulo village as a pilot model for freshwater fishery technoparks and identify supporting factors in the development of village potential management as a technopark tourism destination in Aceh Besar District. This study uses qualitative methods with field observations, including interviews and documentation, as well as data analysis. The results of the study show that indicators of the potential of technopark villages include land and infrastructure capabilities, agroecology, creating added value, employment opportunities, government support, and research and development institutions, which show a value of 75.88% in the high category. Therefore, it can be concluded that Dham Pulo Village has high potential and is feasible to be used as a technopark area. However, to increase the potential and make Dham Pulo Village a technopark tourism village, formal regulatory support from the government is needed. Cultivators are limited in their development of land used for cultivation because it belongs to the government.Keywords: Dham Pulo; fisheries; freshwater; Potential; techno Park